Covid-19 Pandemic as the Reasoning of Force Majeure towards Financing in Islamic Banking - Riska Wijayanti; Ani Yunita (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
This paper analyzes the Covid-19 pandemic as a reason for force majeure in non-performing loan and legal effort its. This juridical-normative research uses a conceptual, statutory and case approach. Analysis using prescriptive with logic and legal reasoning. The results show, the Covid-19 pandemic cannot automatically be used as a reason for force majeure, even though it is designated as a non- 220 Covid-19 Pandemic as the Reasoning of Force Majeure towards Financing ... (Riska Wijayanti) Vol 18 No 2, Desember 2020 ISSN 1829-7382 (Print) 2502-7719 (Online) natural national disaster because to find out which debtors are affected by the pandemic and the payment difficulties, should be proven through the decision of the Religious Court and must fulfil the elements in Article 1244 and 1245 Civil Code. Legal efforts to settle non-performing loans are rescue and settlement. The rescue is carried out by minimizing financial costs and restructuring financing. Settlement can be made by seeking through an auction or by executing the guarantee. The last alternative is resolved through the Religious Court. The legal effort of future for the rescue of non-performing loan that occurred due to the spread of the Covid-19 Pandemic is by renegotiating, whereby making new contracts or issuing addendums that bind the parties and must be implemented in good faith. Therefore, the ius constituendum is indispensable for the settlement of non-performing loan that caused by the pandemic through the OJK Regulation.